(m-3n)(2m+n)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 22:50:15
(m-3n)(2m+n)(m-3n)(2m+n)(m-3n)(2m+n)=2m²+mn-6mn-3n²=2m²-5mn-3n²2m^2-5mn-3n^2
(m-3n)(2m+n)
(m-3n)(2m+n)
(m-3n)(2m+n)
=2m²+mn-6mn-3n²
=2m²-5mn-3n²
2m^2-5mn-3n^2
[(m-n)^2*(m-n)^3]^2/(m-n)^4
[(m-n)^2*(m-n)^3]^2/(m-n)^4
3m(m-n)-2n(m-n)的平方
因式分解(n-m)^3(m-n)^2-(m-n)^5
(m-n)2(n-m)3(n-m)4化简
(n-m)^3×(m-n)^2-(m-n)^5
计算(m+n)^3-(n+m)(m-n)^2
(m-n)^3(n-m)^2(m-n)=_____
4m(m-n)^2+4n(n-m)^3
2(m-n)的2次-(m+n)(m-2n)-3n(n-m)
(m-n)3-(2n-m)3
2m-3n-m+2n
(3m-n)(m-2n)=()
(m+2n)(m-3n)
(m-3n)(2m+n)
约分(m-n)^2/(n-m)^3
(1),(-m-n)(-m+n) (2),(-m+n)(m-n)
(m-2n)(-m-n)